Prevalence of gastrointestinal parasites in three groups of domestic poultry managed under backyard system in the Savanna subregion, Department of Sucre, Colombia (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: To identify the prevalence of gastrointestinal parasites that affect the backyard poultry system in the Savanna region, Department of Sucre, Colombia.  Materials and Methods: Fecal samples were collected from 860 native birds, both hens (Gallus domesticus), ducks (Anas platyrhynchos domesticus), and turkeys (Meleagris gallopavo), regardless of age and sex. Samples were processed using direct techniques with ZnSO4 and indirect methods such as modified Sloss. Data were presented as frequencies, and the nonparametric odds ratio test was used for two independent samples.  Results: A total of 77.3% (665/860) of the birds were infected with one or more species of gastrointestinal parasites. Among the nematodes, Capillaria spp. (45.6%), Ascaridia galli (18.4%), Heterakis gallinarum (59.4%), Syngamus trachea (38.9%), Tetrameres spp. (25.2%), and Strongylus spp. (12.2%) were recorded. The cestodes were Choanotaenia infundibulum (22.6%), Davainea proglottina (42.3%), Raillietina spp. (58.3%), and Hymenolepis spp. (54.7%), while only Eimeria spp. (90%) was recorded as protozoa.  Conclusions: The study showed a high incidence of gastrointestinal parasite infestations, the most common species being Hymenolepis spp., Eimeria spp., Raillietina spp., and Heterakis gallinarum.J. Adv. Vet. Anim. Res., 8(4): 606–611, December 2021http://doi.org/10.5455/javar.2021.h551